2010
DOI: 10.17161/kjm.v3i2.11311
|View full text |Cite
|
Sign up to set email alerts
|

Use of the QuantiFERON®-TB Gold Assay in Pregnant Patients

Abstract: Background. The QuantiFERON ® -TB Gold assay is a new test for latent tuberculosis infection. It is thought to be more reliable and have fewer false positives than the tuberculin skin test (TST). Both tests are dependent on a normal immune system for diagnostic accuracy. However, no comparisons of the two tests have assessed the accuracy in pregnant women. This investigation assessed the consistency of results between the two tests in both pregnant and nonpregnant women. Methods. The study included 152 women p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In addition, this study demonstrated that the concordance between TST and QFTGIT increased in the presence of pregnancy or HIV infection, with the highest agreement appearing in women with both conditions. In agreement with this finding, previous studies also showed an increased concordance of TST and QFTGIT in HIV-positive compared to HIV-negative individuals (Lin et al, 2016) as well as in pregnant compared to non-pregnant women (Chehab et al, 2010). The increased agreement due to the underlying HIV infection and pregnancy could be related to the selection of participants with better immune competency and deteriorated sensitivity of the tests, resulting in a higher concordance between TST and QFTGIT results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, this study demonstrated that the concordance between TST and QFTGIT increased in the presence of pregnancy or HIV infection, with the highest agreement appearing in women with both conditions. In agreement with this finding, previous studies also showed an increased concordance of TST and QFTGIT in HIV-positive compared to HIV-negative individuals (Lin et al, 2016) as well as in pregnant compared to non-pregnant women (Chehab et al, 2010). The increased agreement due to the underlying HIV infection and pregnancy could be related to the selection of participants with better immune competency and deteriorated sensitivity of the tests, resulting in a higher concordance between TST and QFTGIT results.…”
Section: Discussionsupporting
confidence: 81%
“…This could be due to the waning effect of childhood BCG vaccination over time in women of reproductive age. However, prior BCG vaccination was associated with positivity of TST but not QFTGIT (Chehab et al, 2010;Worjoloh et al, 2011) because the PPD used in TST is also present in the BCG vaccine whereas antigens used in QFTGIT are specific to M. tuberculosis (Huebner et al, 1993;Wang et al, 2002). Furthermore, although this study and others (LaCourse et al, 2017;Latorre et al, 2010) showed that HIV-positive women with elevated CD4 + T-cell count had a relatively higher detection rate of LTBI by these tests, there was no significant association between the positive TST and QFTGIT results and the CD4 + T-cell count.…”
Section: Discussionmentioning
confidence: 83%
“…(3133) In the only other study we know of that compared tuberculin skin test and interferon gamma release assay results in healthy pregnant women, Chehab et al found 91% agreement between tuberculin skin test and interferon gamma release assay among pregnant women in Kansas. (17) However, the prevalence of tuberculin skin test or interferon gamma release assay positivity was very low in this study population (less than 10% of positive tuberculin skin test and less than 5% of positive interferon gamma release assay), which may explain the higher agreement between the two tests. (34)…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, few studies have evaluated the use of interferon gamma release assays in normal pregnancy. (17)…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of discordance (IGRA+/TST−) differs from the predominant discordance pattern (TST+/IGRA−) observed in studies of HIV-negative pregnant women in low TB incidence settings. [1214] In settings with lower risk of TB transmission, a positive TST may reflect false positivity due to BCG vaccination rather than Mtb infection, leading to a higher proportion of TST+/IGRA−. [15] Additionally, most studies have been cross-sectional, and do not capture potential dynamic effects of peripartum stage on LTBI diagnostics.…”
Section: Introductionmentioning
confidence: 99%